Exploring adaptive approaches for social-ecological sustainability in the Belt and Road countries: From the perspective of ecological resource flow. (1st June 2022) - Yan, Huimin; Du, Wenpeng; Feng, Zhiming; Yang, Yanzhao; Xue, Zhichao
Abstract: The countries along the Belt and Road (B&R) are characterized by fragile ecosystems and underdevelopment economy. International trade usually transferred the eco-environmental negative impacts to developing countries. How to avoid the conflict between economic development and eco-environmental protection is the primary concern of building the Green Silk Road. To discover the adaptive strategies for ensuring the sustainability of the social-ecosystem in countries along the B&R, this study analyzes the supply-consumption relationship of ecological resources by simulating the flow of net primary productivity between the ecosystem and the social system. The results show that: (1) The flow of ecological resources between agricultural and husbandry systems have effectively alleviated the local ecological pressure caused by animal husbandry in countries along the B&R. Animal husbandry in developed countries economize the local ecological resources by importing feed, while mitigating the grazing pressure by utilizing the local crop residues in underdeveloped agricultural countries. (2) International trade not only enables countries with insufficient ecological resources to meet their demands by importing ecological products and thus alleviate ecosystem pressure, but also promotes countries with sufficient ecological resources to transform their resource advantages into economic advantages by exporting without at the expense of ecological sustainability. (3) For underdeveloped countries, the dependence of economic development on ecological resources is at the expense of the living demands of residents, only if the economy could have leap-forward improvement the allocation of ecological resources within the social system would be inclined to living demands. These adaptive approaches not only provide the evidences of ecological-social sustainable development by promoting the reasonable flow and allocation of ecological resources, but also imply the necessary assistance for the underdeveloped countries to guarantee the basic human well-being in economic development. Graphical abstract: Image 1 Highlights: Explore adaptive strategies for enhancing sustainability based on existing experience. Crop residues used in livestock production effectively relieves ecological pressure. International trade can alleviate ecological pressures in resource-poor regions. International trade can transform resource advantages into economic advantages. Underdeveloped countries sacrifice human well-being to balance development and protection.